Pengabdian Internasional: Pelestarian dan Food Estate Melalui Penanaman Pohon di Ekowisata Beras Basah - saragih, Wismaroh Sanniwati; Bejo Slamet; Shiroishi Hidetoshi; Irwan Agusnu Putra; Razali; Lisnawita; Sijabat, Octanina Sari; Dedi Kurniawan (JURNAL ABDIMAS MADUMA, 2025)
Indonesia, as a tropical country, faces significant challenges in preserving its mangrove forests, particularly in the Beras Basah Ecotourism Area, Langkat Regency, which holds high ecological and economic potential. The food estate in mangrove forests aims to develop land for food production, specifically as a source of forage for stingless bees. This community service project aims to preserve the food estate through tree planting in the Beras Basah Ecotourism Area. The methodology includes interviews and discussions, involving 22 participants from Universitas Tjut Nyak Dhien, Tottori University Japan, and Universitas Sumatra Utara. The project results indicate a decline in the stingless bee population due to limited food sources from the mangrove area. Planting fruit trees such as water guava, stone guava, and mango is expected to provide ecological benefits, attract tourists, and support the development of a food estate for stingless bees. With a sustainable approach, this food estate program can serve as a model for the development of mangrove forests as ecotourism areas and strengthen food security in the Beras Basah village, Langkat, North Sumatra. Keywords : Ecotourism; food estate; mangrove; stingless bees